Vacuum hot press forming process of silicone-polyimide composite sealant layer
Patent Information
- Application Number
- CN202611102685.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-09
AI Technical Summary
然而,这些方法在制备密封胶层时存在以下突出问题:第一,界面相容性差
本发明通过采用偶联剂对基材进行表面预处理,在基材与复合胶层之间形成化学键合界面,从根本上解决了有机硅-聚酰亚胺复合材料与基材粘接性差的问题;
Smart Images

Figure CN122875455A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer material processing technology, specifically to a vacuum hot pressing process for an organosilicon-polyimide composite sealant layer. Background Technology
[0002] Silicone resins are widely used as sealing materials due to their excellent high and low temperature resistance (-60℃ to 300℃), good flexibility, and electrical insulation. However, pure silicone resins have low mechanical strength, poor tear resistance, and are prone to degradation at high temperatures, limiting their application in harsh working conditions. Polyimide resins possess extremely high thermal stability (long-term operating temperature up to 350℃), excellent mechanical strength, and radiation resistance, but they are difficult to process, costly, and have poor adhesion to substrates such as metals. Combining silicone and polyimide promises to combine the advantages of both, resulting in a sealing material that combines high temperature resistance, high strength, good adhesion, and flexibility.
[0003] Currently, the main methods for preparing silicone-polyimide composites include solution blending, sol-gel, and in-situ polymerization. However, these methods have the following prominent problems in preparing sealant layers: First, poor interfacial compatibility. The solubility parameters of silicone and polyimide differ significantly, and simple blending easily leads to macroscopic phase separation, resulting in a decrease in the mechanical and sealing properties of the composite material. Second, difficulty in removing air bubbles during curing. During imidization, the polyimide precursor releases small molecule byproducts (such as water). If these are not removed in time, they will form bubbles or pinholes inside the adhesive layer, severely reducing sealing reliability. Third, difficulty in controlling thickness uniformity. Traditional coating or casting methods struggle to obtain uniformly thick adhesive layers over large areas, and curing shrinkage can lead to stress concentration and warping deformation. Fourth, lack of systematic optimization of hot-pressing process parameters. In existing technologies, parameters such as hot-pressing temperature, pressure, and vacuum degree largely rely on empirical settings, lacking scientific consideration of the synergistic matching of silicone crosslinking and polyimide imidization kinetics, resulting in unstable final product performance.
[0004] In view of this, we propose a vacuum hot pressing process for silicone-polyimide composite sealant layers. Summary of the Invention
[0005] The purpose of this invention is to provide a vacuum hot pressing process for silicone-polyimide composite sealant layers to solve the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A vacuum hot pressing process for forming an organosilicon-polyimide composite sealant layer, the process comprising: S1. Clean and dry the surface of the substrate to be sealed, and then perform surface treatment with a coupling agent solution to form a chemically active layer on the substrate surface. S2. Mix the silicone resin and polyimide precursor solution at a mass ratio of 1:0.5 to 1:2, add 0.5%-3% of crosslinking agent and 0.1%-1% of catalyst according to the total mass of the mixed resin, stir evenly and then degas under vacuum to obtain a uniform composite adhesive. S3. Apply the composite adhesive obtained in step S2 evenly to the surface of the substrate treated in step S1, control the coating thickness to be 0.1-2 mm, and then pre-cur it at 80-120℃ for 10-30 minutes to make the adhesive layer reach the B-stage gel state. S4. Place the pre-cured workpiece obtained in step S3 into a vacuum hot press, evacuate to a vacuum degree ≤100Pa, and then execute a multi-stage pressurization and heating program: the first stage is held at 80-120℃ and 0.1-0.5MPa for 10-20 minutes; the second stage is heated at 2-5℃ / min to 150-200℃ and pressure increased to 1-3MPa for 20-40 minutes; the third stage is heated at 2-5℃ / min to 250-300℃ and pressure increased to 3-5MPa for 30-60 minutes; then cool down to below 60℃ at 1-3℃ / min to release the pressure, and obtain a pre-cured composite adhesive layer; S5. Place the workpiece obtained in step S4 in an inert atmosphere furnace and keep it at 300-350℃ for 1-3 hours to complete the complete imidization reaction of the polyimide precursor. After cooling, the silicone-polyimide composite sealant layer is obtained.
[0007] Preferably, in step S1, the coupling agent is at least one of γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane, with a solution concentration of 0.5-5 wt%, the solvent is a mixture of ethanol and water, the treatment temperature is 80-120°C, and the treatment time is 30-60 minutes.
[0008] Preferably, in step S2, the organosilicon resin is methylphenyl silicone resin or methyl vinyl silicone resin, with a number average molecular weight of 2000-10000 and a phenyl content of 10-40 mol%; the polyimide precursor solution is a polyamic acid solution obtained by polycondensation of pyromellitic dianhydride and 4,4'-diaminodiphenyl ether in a polar solvent, with a solid content of 15-30 wt%.
[0009] Preferably, in step S2, the crosslinking agent is at least one of dicumyl peroxide or 2,5-dimethyl-2,5-di-tert-butylperoxide; and the catalyst is at least one of aluminum acetylacetonate or dibutyltin dilaurate.
[0010] Preferably, in step S3, the coating is performed by blade coating, roller coating or screen printing. The coating thickness is controlled by the gap between the blades or the thickness of the screen. After coating, the coating is allowed to stand at room temperature for 5-15 minutes to allow the adhesive to flow and level before pre-curing.
[0011] Preferably, in step S4, the surface of the pressure plate of the vacuum hot press is provided with a microgroove structure, the groove depth is 0.1-0.5mm and the spacing is 1-5mm, so as to guide the gas out during the hot pressing process.
[0012] Preferably, in step S4, the pressure switching point and temperature switching point in the multi-segment pressurization and heating program are synchronized, and the densification endpoint is determined by real-time monitoring of the adhesive layer thickness change at the end of each heat preservation segment. When the thickness change rate is less than 0.5% / min, the program automatically enters the next segment.
[0013] Preferably, in step S5, the inert atmosphere is nitrogen or argon, and the gas flow rate is 100-500 sccm; the cooling method is natural cooling with the furnace, and the cooling rate is controlled at 2-5℃ / min.
[0014] Preferably, between step S3 and step S4, the process further includes: laying a layer of fiber-reinforced fabric pretreated with a coupling agent on the surface of the pre-cured adhesive layer. The fiber-reinforced fabric is glass fiber cloth, aramid fiber cloth, or carbon fiber cloth, with a surface density of 20-100 g / m³. 2 Then, vacuum hot pressing is performed.
[0015] Preferably, the substrate is stainless steel, aluminum alloy, ceramic or polyimide composite material; the final composite sealant layer has a thickness of 0.2-3 mm, a peel strength of not less than 5 N / mm, a thermal decomposition temperature of not less than 450℃, and a compression set of not more than 15% at 200℃.
[0016] By employing the above technical solution, the present invention provides a vacuum hot pressing process for forming an organosilicon-polyimide composite sealant layer. It possesses at least the following beneficial effects: This invention solves the problem of poor adhesion between organosilicon-polyimide composite materials and substrates by using a coupling agent to pretreat the surface of the substrate and forming a chemical bonding interface between the substrate and the composite adhesive layer. By employing a vacuum hot pressing process that includes a three-stage heating-pressing gradient, the kinetic matching of organosilicon crosslinking and polyimide imidization was achieved, as well as the complete elimination of air bubbles, thus solving the problems of air bubble defects and thickness uniformity during the curing process. By premixing organosilicon resin and polyimide precursor in solution and adding crosslinking agent and catalyst, uniform dispersion of the two phases at the molecular level was achieved, avoiding macroscopic phase separation. By employing an inert atmosphere and precise temperature control in the post-curing step, complete imidization of the polyimide precursor is ensured, while preventing the oxidative degradation of silicone at high temperatures. Attached Figure Description
[0017] The accompanying drawings, which are provided to further illustrate the invention, constitute a part of this application: Figure 1 This is a schematic diagram of the overall process of vacuum hot pressing molding of an organosilicon-polyimide composite sealant layer according to the present invention. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Please see Figure 1 , Figure 1 This is a schematic diagram of the overall process of vacuum hot pressing molding of an organosilicon-polyimide composite sealant layer according to the present invention; the present invention provides a vacuum hot pressing molding process for an organosilicon-polyimide composite sealant layer, including: Step S1: Clean and dry the surface of the substrate to be sealed, and then perform surface treatment with a coupling agent solution to form a chemically active layer on the substrate surface; It should be noted that step S1 aims to address the fundamental problem of poor adhesion between the silicone-polyimide composite adhesive layer and the substrate. The substrate surface typically contains oil, oxide layers, or adsorbed water molecules, which hinder effective contact between the adhesive layer and the substrate. Cleaning (e.g., ultrasonic cleaning with acetone, ethanol, and deionized water sequentially) removes surface organic matter and particulate impurities, while drying removes residual moisture. The subsequent coupling agent (e.g., γ-aminopropyltriethoxysilane) is a bifunctional molecule: its ethoxysilane group at one end can condense with hydroxyl groups on the substrate surface (e.g., M-OH on a metal surface) after hydrolysis to form a covalent bond; the amino or epoxy group at the other end can chemically react with the silicone resin and polyimide precursor. This "molecular bridging" effect transforms the interface, which was originally based solely on physical adsorption, into a chemically bonded interface, significantly improving peel strength. The concentration of the coupling agent (0.5-5wt%) and the treatment conditions (80-120℃, 30-60 minutes) need to be precisely controlled: if the concentration is too low, the surface coverage will be insufficient, and if the concentration is too high, a weak boundary layer will be formed, which will reduce the binding force.
[0020] Step S2: Mix the silicone resin and polyimide precursor solution at a mass ratio of 1:0.5 to 1:2, add 0.5%-3% of crosslinking agent and 0.1%-1% of catalyst according to the total mass of the mixed resin, stir evenly and then degas under vacuum to obtain a uniform composite adhesive. It should be noted that step S2 determines the homogeneity and reaction characteristics of the composite adhesive. The silicone resin and the polyimide precursor (polyamic acid solution) differ in solubility parameters, and simple mixing easily leads to phase separation. This invention utilizes the good solubility of a polar solvent (such as N-methylpyrrolidone) to mix the two polymer chains in solution, causing them to entangle at the molecular level and form a homogeneous mixture. A mass ratio of 1:0.5 to 1:2 is critical: too high a silicone ratio limits the improvement in the mechanical strength and heat resistance of the composite material; too high a polyimide ratio reduces the flexibility of the adhesive layer and increases costs. The crosslinking agent (such as dicumyl peroxide) initiates the vinyl crosslinking reaction of the silicone resin under hot pressing, forming a three-dimensional network structure; the catalyst (such as aluminum acetylacetonate) catalyzes the imidization reaction of the polyamic acid. The amounts of both must balance the reaction rate and the operating time: too much crosslinking agent and catalyst will cause the adhesive to gel before coating, while too little will result in incomplete curing. Vacuum degassing is performed at room temperature to remove air trapped during stirring and prevent bubble defects from forming during subsequent hot pressing.
[0021] Step S3: Apply the composite adhesive obtained in step S2 evenly to the surface of the substrate treated in step S1, control the coating thickness to be 0.1-2 mm, and then pre-cur it at 80-120℃ for 10-30 minutes to make the adhesive layer reach the B-stage gel state. It should be noted that step S3 involves fixing the composite adhesive onto the substrate and achieving an intermediate state suitable for subsequent hot pressing. The coating thickness of 0.1-2mm needs to be determined based on the final sealing requirements: too thin and the sealing effect will be insufficient; too thick and the adhesive will easily overflow during hot pressing, and internal air bubbles will be difficult to expel. After coating, allow it to stand at room temperature for 5-15 minutes to allow the adhesive to level out, which can eliminate scraper marks and obtain a uniform initial thickness. The pre-curing temperature of 80-120℃ and the time of 10-30 minutes need to be precisely controlled so that the adhesive layer reaches the "B-stage" state—that is, the adhesive has lost its fluidity but has not yet fully cured. In this state, the adhesive layer has a certain self-supporting ability, which is convenient for transfer to the hot press; at the same time, it can soften and flow again during subsequent hot pressing, filling the microscopic unevenness of the substrate surface and achieving a tight bond. If the pre-curing is insufficient, the adhesive layer is prone to deformation during transfer; if the pre-curing is excessive, the adhesive layer cannot flow sufficiently during hot pressing, affecting the densification effect.
[0022] Step S4: Place the pre-cured workpiece obtained in step S3 into a vacuum hot press, evacuate to a vacuum degree ≤100Pa, and then execute a multi-stage pressurization and heating program: the first stage is held at 80-120℃ and 0.1-0.5MPa for 10-20 minutes; the second stage is heated at 2-5℃ / min to 150-200℃ and pressure increased to 1-3MPa for 20-40 minutes; the third stage is heated at 2-5℃ / min to 250-300℃ and pressure increased to 3-5MPa for 30-60 minutes; then cool down to below 60℃ at 1-3℃ / min to release the pressure, and obtain a pre-cured composite adhesive layer; It should be noted that step S4 solves the three major problems of bubble removal, interface bonding, and densification through the synergistic effect of vacuum environment and multi-stage gradient hot pressing. The vacuum environment (≤100Pa) removes the air between the adhesive layer and the substrate interface, as well as the gas in the micropores inside the adhesive layer, before hot pressing, creating air gap-free contact conditions for subsequent hot pressing. The three-stage pressurization and heating program is designed based on the kinetic characteristics of silicone crosslinking and polyimide imidization: The first stage (80-120℃, 0.1-0.5MPa) has a temperature lower than the silicone crosslinking initiation temperature (approximately 130℃). During this stage, the adhesive layer softens and levels, and the low pressure prevents the adhesive from being squeezed out, while the vacuum continues to expel residual gas; The second stage (150-200℃, 1-3MPa) enters the silicone crosslinking window (130-200℃), where the peroxide decomposes to generate free radicals that initiate the crosslinking reaction. At the same time, the polyamic acid begins partial imidization (150-200℃), releasing water molecules. Increasing the pressure to 1-3MPa promotes the crosslinking reaction and forces the released water molecules to the edge of the adhesive layer for discharge; The third stage (250-300℃, 3-5MPa) completes the imidization of the polyimide (>250℃), and the high pressure fully densifies the adhesive layer, eliminating residual micropores. The cooling rate of 1-3℃ / min needs to be controlled slowly to prevent the adhesive layer from cracking or separating from the substrate due to thermal stress.
[0023] Step S5: Place the workpiece obtained in step S4 in an inert atmosphere furnace and keep it at 300-350℃ for 1-3 hours to complete the complete imidization reaction of the polyimide precursor. After cooling, the silicone-polyimide composite sealant layer is obtained. It should be noted that step S5 is the key step for final curing and performance stabilization. The hot-pressing temperature (maximum 250-300℃) and holding time (30-60 minutes) in step S4 are insufficient to completely imidize the polyamic acid (usually above 300℃ and above 1 hour are required to achieve an imidization degree of over 98%). Therefore, post-curing treatment is required in an inert atmosphere oven. The role of the inert atmosphere (nitrogen or argon) is to prevent the silicone resin from undergoing oxidative degradation at high temperatures—the methyl groups of the silicone side chains are easily oxidized to hydroxyl groups in air above 300℃, leading to the destruction of the cross-linking network. The post-curing temperature of 300-350℃ and the time of 1-3 hours need to be adjusted according to the thickness of the adhesive layer: thicker samples require a longer time to ensure uniform internal temperature and complete the imidization reaction. The cooling method is natural cooling in the oven, with the cooling rate controlled at 2-5℃ / min to avoid stress accumulation caused by excessively rapid cooling.
[0024] In step S1, the coupling agent is at least one of γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane, with a solution concentration of 0.5-5wt%, a solvent of ethanol and water, a treatment temperature of 80-120℃, and a treatment time of 30-60 minutes. It should be noted that the selection of coupling agent needs to be determined based on the substrate type and the chemical properties of the adhesive layer. The terminal amino group of γ-aminopropyltriethoxysilane (KH-550) can react with the carboxyl group of the polyimide precursor, making it suitable for polyimide-based systems. The terminal epoxy group of γ-glycidoxypropyltrimethoxysilane (KH-560) can react with the hydroxyl or carboxyl groups of the silicone resin, making it suitable for silicone-based systems. A mixture of ethanol and water (e.g., 9:1 volume ratio) is used as the solvent. Ethanol dissolves the coupling agent, while water promotes the hydrolysis of silane to generate silanol groups (Si-OH), which is a prerequisite for condensation with the hydroxyl groups on the substrate surface. A treatment temperature of 80-120℃ can accelerate the condensation reaction and evaporate the solvent, while a treatment time of 30-60 minutes ensures a complete reaction. The concentration of 0.5-5wt% needs optimization: if the concentration is too low, the coupling agent molecules cannot form a continuous monolayer coverage; if the concentration is too high, multilayer physical adsorption occurs, which reduces the bonding strength.
[0025] In step S2, the organosilicon resin is methylphenyl silicone resin or methyl vinyl silicone resin, with a number-average molecular weight of 2000-10000 and a phenyl content of 10-40 mol%; the polyimide precursor solution is a polyamic acid solution obtained by polycondensation of pyromellitic dianhydride and 4,4'-diaminodiphenyl ether in a polar solvent, with a solid content of 15-30 wt%. It should be noted that the type and molecular weight of silicone resin directly affect the performance of composite materials. The introduction of phenyl groups into methylphenyl silicone resin improves its heat resistance and compatibility with polyimides; while the presence of vinyl groups in methylvinyl silicone resin allows for network structure formation through peroxide crosslinking. The selection of a number-average molecular weight of 2000-10000 requires a balance between processability and mechanical properties: too low a molecular weight results in insufficient crosslinking density and low strength after curing; too high a molecular weight leads to excessive viscosity and difficulty in coating. The phenyl content of 10-40 mol% affects heat resistance and flexibility: higher phenyl content results in better heat resistance but decreased flexibility. The polyimide precursor, polyamic acid obtained by the condensation polymerization of pyromellitic dianhydride (PMDA) and 4,4'-diaminodiphenyl ether (ODA), is a classic polyimide precursor system, exhibiting excellent thermal stability and mechanical strength after imidization. The solid content needs to be controlled between 15-30 wt%: if the solid content is too low, the solvent will evaporate a lot and shrink severely during coating; if the solid content is too high, the viscosity of the adhesive will be too high and it will not be conducive to uniform mixing.
[0026] In step S2, the crosslinking agent is at least one of dicumyl peroxide or 2,5-dimethyl-2,5-di-tert-butylperoxide; the catalyst is at least one of aluminum acetylacetonate or dibutyltin dilaurate. It should be noted that the selection of crosslinking agents and catalysts must match the reaction characteristics of the silicone resin and polyimide precursor. Dicumyl peroxide (DCP) and 2,5-dimethyl-2,5-di-tert-butylperoxide (DBPH) are both organic peroxides. When heated to their decomposition temperatures (approximately 130°C for DCP and 150°C for DBPH), they generate free radicals, initiating the crosslinking reaction of vinyl groups in the silicone resin. Their half-lives differ, and they can be selected or used in combination according to process requirements. Aluminum acetylacetonate is a commonly used catalyst for the imidization of polyamic acids, lowering the activation energy of the imidization reaction through coordination. Dibutyltin dilaurate is a catalyst for the condensation reaction of silicones, promoting the condensation between silanol groups. The catalyst dosage (0.1%-1%) needs to be precisely controlled: insufficient dosage will result in insignificant catalytic effects, while excessive dosage may lead to catalytic side reactions or affect the storage stability of the adhesive.
[0027] In step S3, the coating is carried out by blade coating, roller coating or screen printing. The coating thickness is controlled by the gap of the blade or the thickness of the screen. After coating, the adhesive is allowed to stand at room temperature for 5-15 minutes to allow the adhesive to flow and level before pre-curing. It should be noted that the choice of coating method must be determined based on the shape, area, and precision requirements of the substrate. Blade coating is suitable for flat substrates, allowing for precise control of coating thickness by adjusting the blade gap; roller coating is suitable for continuous roll materials, offering high efficiency but slightly lower precision; screen printing is suitable for patterned coatings or curved substrates. After coating, allow the adhesive to stand at room temperature for 5-15 minutes to level. This step is crucial for eliminating coating marks and achieving a uniform thickness. The leveling time needs to be adjusted according to the adhesive viscosity: if the viscosity is too high, leveling is slow, and the standing time can be appropriately extended or the viscosity slightly heated to reduce it; however, excessive standing time may lead to excessive solvent evaporation and an increase in adhesive viscosity, which in turn affects the leveling effect.
[0028] In step S4, the surface of the pressure plate of the vacuum hot press is provided with a microgroove structure, the groove depth is 0.1-0.5mm and the spacing is 1-5mm, so as to guide the gas out during the hot pressing process; It should be noted that the microgroove structure on the surface of the pressure plate is an ingenious engineering design. During hot pressing, residual gas or water vapor released from imidization may exist inside the adhesive layer and at the interface. If these cannot be discharged in time, they will form bubbles or pinhole defects inside the adhesive layer. The microgrooves (0.1-0.5 mm deep, 1-5 mm spacing) provide a directional discharge channel for the gas: under pressure, the gas flows along the groove direction towards the edge of the pressure plate and is eventually removed by the vacuum system. The groove depth and spacing need to be optimized according to the adhesive layer thickness and viscosity: if the grooves are too shallow, venting will be inefficient; if they are too deep, they may leave marks on the adhesive layer surface. If the spacing is too small, the number of grooves will be too large, affecting the rigidity of the pressure plate; if the spacing is too large, the venting distance will be too long. For high-viscosity adhesives, the groove depth can be increased or the spacing can be reduced appropriately.
[0029] In step S4, the pressure switching point and temperature switching point in the multi-segment pressurization and heating program are synchronized, and the densification endpoint is determined by real-time monitoring of the adhesive layer thickness change at the end of each heat preservation stage. When the thickness change rate is less than 0.5% / min, the program automatically enters the next stage. It is worth noting that the synchronized switching of pressure and temperature, as well as the endpoint determination based on thickness changes, are intelligent control features of this invention. The synchronized switching of pressure and temperature ensures that the rheological state of the adhesive layer matches the applied pressure at each stage: at low temperatures, the adhesive layer viscosity is high, and low pressure can prevent the adhesive from being extruded; at high temperatures, the adhesive layer viscosity decreases, requiring high pressure for effective densification. Real-time monitoring of adhesive layer thickness changes (e.g., via displacement sensors or laser rangefinders) is key to achieving adaptive control: during each insulation stage, the adhesive layer thickness gradually decreases due to leveling, venting, and cross-linking shrinkage; when the thickness change rate is less than 0.5% / min, it indicates that the physical or chemical process of that stage is essentially complete, and the system automatically switches to the next stage. This closed-loop control method avoids over- or under-insulation that may result from fixed-time insulation, significantly improving process adaptability and product consistency.
[0030] In step S5, the inert atmosphere is nitrogen or argon, and the gas flow rate is 100-500 sccm; the cooling method is natural cooling with the furnace, and the cooling rate is controlled at 2-5℃ / min. It is worth noting that the choice of inert atmosphere and the control of gas flow rate are crucial to the post-curing effect. Nitrogen is the preferred inert gas due to its low cost and wide availability; argon has a high density and low thermal conductivity, providing better thermal insulation, but it is more expensive. A gas flow rate of 100-500 sccm is sufficient to remove water vapor released during imidization and possible pyrolysis byproducts, but excessive flow rate may cause turbulence in the furnace and affect temperature uniformity. Natural cooling with the furnace and controlling the cooling rate at 2-5℃ / min is to avoid thermal stress concentration caused by excessively rapid cooling. The coefficient of thermal expansion of the silicone-polyimide composite material is different from that of the metal substrate; rapid cooling will generate shear stress at the interface, which may lead to cracking or peeling of the adhesive layer. Slow cooling allows stress to be released gradually, ensuring the integrity of the interface.
[0031] Between steps S3 and S4, there is an additional step of laying a reinforcing layer: a layer of fiber-reinforcing cloth pretreated with a coupling agent is laid on the surface of the pre-cured adhesive layer. The fiber-reinforcing cloth is glass fiber cloth, aramid fiber cloth, or carbon fiber cloth, with a surface density of 20-100 g / m³. 2 Then, vacuum hot pressing is performed; It is worth noting that adding a reinforcing layer is an optional strengthening measure, suitable for applications requiring higher mechanical strength or tear resistance. Fiber-reinforced fabrics (glass fiber, aramid fiber, or carbon fiber) possess high tensile strength and modulus; when embedded in the adhesive layer, they can significantly improve the overall mechanical properties of the composite sealant layer, particularly tear strength and puncture resistance. The fiber fabric needs to be pretreated with a coupling agent to ensure good interfacial bonding between it and the silicone-polyimide matrix, preventing the fiber-matrix interface from becoming a new weak point. Areal density: 20-100 g / m³ 2 The choice of adhesive layer thickness needs to balance the reinforcement effect: if the areal density is too low, the reinforcement effect will be limited; if the areal density is too high, the adhesive layer will not be able to fully impregnate the fibers and will easily form pores. The timing of laying should be after pre-curing and before hot pressing. At this time, the adhesive layer is in the B-stage state, which has a certain degree of stickiness but is not fully cured, which can firmly fix the position of the fiber cloth and prevent the fibers from shifting during hot pressing.
[0032] The substrate is stainless steel, aluminum alloy, ceramic, or polyimide composite material; the final composite sealant layer has a thickness of 0.2-3 mm, a peel strength of not less than 5 N / mm, a thermal decomposition temperature of not less than 450℃, and a compression set of not more than 15% at 200℃. It is worth noting that stainless steel and aluminum alloys are common metal sealing substrates, with natural oxide layers on their surfaces that can be bonded by coupling agents; ceramic substrates are rich in hydroxyl groups, exhibiting high reactivity with silane coupling agents; and polyimide composite materials are themselves high-temperature resistant materials, exhibiting excellent compatibility with the composite adhesive layer produced in this process. The performance indicators of the final product demonstrate the technical advantages of this invention: peel strength not less than 5 N / mm (far higher than the 1-2 N / mm of traditional physical adsorption), ensuring the reliability of the sealing interface; thermal decomposition temperature not less than 450℃, meeting the requirements for high-temperature applications; and compression set at 200℃ not greater than 15%, indicating that the adhesive layer maintains good elastic recovery under long-term pressure, a key performance indicator for sealing materials. The adhesive layer thickness of 0.2-3 mm can be adjusted according to specific sealing gaps and pressure requirements.
[0033] Example 1 S1. Take a stainless steel substrate (50mm×50mm×2mm) and ultrasonically clean it sequentially with acetone, ethanol, and deionized water for 10 minutes each, then dry it at 100℃ for 30 minutes. Prepare a 1wt% γ-aminopropyltriethoxysilane ethanol / water (volume ratio 9:1) solution, immerse the substrate in the solution, treat it at 100℃ for 45 minutes, remove it, rinse it with ethanol, and dry it at 120℃.
[0034] S2. Take 10g of methylphenyl silicone resin (number average molecular weight 5000, phenyl content 25mol%) and mix it with 15g of polyamic acid solution (pyromellitic dianhydride and 4,4'-diaminodiphenyl ether polycondensed in N-methylpyrrolidone, solid content 20wt%). Add 0.3g of dicumyl peroxide and 0.05g of aluminum acetylacetonate. Stir evenly and then degas under vacuum for 15 minutes.
[0035] S3. Apply the composite adhesive to the substrate surface using a scraper with a scraper gap of 0.5mm. Let it stand at room temperature for 10 minutes to level it, and then place it in an oven to pre-cur at 100℃ for 20 minutes.
[0036] S4. Place the pre-cured workpiece into a vacuum hot press and evacuate to 50 Pa. Execute a three-stage program: Stage 1: 100℃, 0.3 MPa, hold for 15 minutes; Stage 2: Increase temperature to 180℃ at 3℃ / min, increase pressure to 2 MPa, hold for 30 minutes; Stage 3: Increase temperature to 280℃ at 3℃ / min, increase pressure to 4 MPa, hold for 45 minutes. Then cool to 50℃ at 2℃ / min and release pressure.
[0037] S5. Place the workpiece in a nitrogen atmosphere furnace with a gas flow rate of 200 sccm, heat it to 320℃ and hold it for 2 hours, then cool it to room temperature with the furnace.
[0038] Performance testing: Adhesive layer thickness 0.41mm, peel strength (180°) 6.2N / mm, thermal decomposition temperature (Td5%) 468℃, compression set at 200℃ 11%, cross-sectional SEM observation showed no bubbles or delamination.
[0039] Example 2 In step S2, the mass ratio of organosilicon to polyamic acid was adjusted to 1:1 (10g each), and the other conditions were the same as in Example 1. The resulting adhesive layer had a peel strength of 5.8 N / mm, a thermal decomposition temperature of 475℃, and a compression set of 9%.
[0040] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0041] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A vacuum hot pressing process for forming an organosilicon-polyimide composite sealant layer, characterized in that, The process includes: S1. Clean and dry the surface of the substrate to be sealed, and then perform surface treatment with a coupling agent solution to form a chemically active layer on the substrate surface. S2. Mix the silicone resin and polyimide precursor solution at a mass ratio of 1:0.5 to 1:2, add 0.5%-3% of crosslinking agent and 0.1%-1% of catalyst according to the total mass of the mixed resin, stir evenly and then degas under vacuum to obtain a uniform composite adhesive. S3. Apply the composite adhesive obtained in step S2 evenly to the surface of the substrate treated in step S1, control the coating thickness to be 0.1-2 mm, and then pre-cur it at 80-120℃ for 10-30 minutes to make the adhesive layer reach the B-stage gel state. S4. Place the pre-cured workpiece obtained in step S3 into a vacuum hot press, evacuate to a vacuum degree ≤100Pa, and then execute a multi-stage pressurization and heating program: the first stage is held at 80-120℃ and 0.1-0.5MPa for 10-20 minutes; the second stage is heated at 2-5℃ / min to 150-200℃ and pressure increased to 1-3MPa for 20-40 minutes; the third stage is heated at 2-5℃ / min to 250-300℃ and pressure increased to 3-5MPa for 30-60 minutes; then cool down to below 60℃ at 1-3℃ / min to release the pressure, and obtain a pre-cured composite adhesive layer; S5. Place the workpiece obtained in step S4 in an inert atmosphere furnace and keep it at 300-350℃ for 1-3 hours to complete the complete imidization reaction of the polyimide precursor. After cooling, the silicone-polyimide composite sealant layer is obtained.
2. The vacuum hot pressing molding process for an organosilicon-polyimide composite sealant layer according to claim 1, characterized in that, In step S1, the coupling agent is at least one of γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane, with a solution concentration of 0.5-5 wt%, a solvent of ethanol and water, a treatment temperature of 80-120°C, and a treatment time of 30-60 minutes.
3. The vacuum hot pressing process for an organosilicon-polyimide composite sealant layer according to claim 1, characterized in that, In step S2, the organosilicon resin is methylphenyl silicone resin or methyl vinyl silicone resin, with a number average molecular weight of 2000-10000 and a phenyl content of 10-40 mol%; the polyimide precursor solution is a polyamic acid solution obtained by polycondensation of pyromellitic dianhydride and 4,4'-diaminodiphenyl ether in a polar solvent, with a solid content of 15-30 wt%.
4. The vacuum hot pressing molding process for an organosilicon-polyimide composite sealant layer according to claim 1, characterized in that, In step S2, the crosslinking agent is at least one of dicumyl peroxide or 2,5-dimethyl-2,5-di-tert-butylperoxide; the catalyst is at least one of aluminum acetylacetonate or dibutyltin dilaurate.
5. The vacuum hot pressing process for an organosilicon-polyimide composite sealant layer according to claim 1, characterized in that, In step S3, the coating is applied by blade coating, roller coating or screen printing. The coating thickness is controlled by the blade gap or screen thickness. After coating, the adhesive is allowed to stand at room temperature for 5-15 minutes to allow it to flow and level before pre-curing.
6. The vacuum hot pressing process for an organosilicon-polyimide composite sealant layer according to claim 1, characterized in that, In step S4, the surface of the pressure plate of the vacuum hot press is provided with a microgroove structure, the groove depth is 0.1-0.5mm and the spacing is 1-5mm, so as to guide the gas out during the hot pressing process.
7. The vacuum hot pressing process for an organosilicon-polyimide composite sealant layer according to claim 1, characterized in that, In step S4, the pressure switching point and temperature switching point in the multi-segment pressurization and heating program are synchronized, and the densification endpoint is determined by real-time monitoring of the adhesive layer thickness change at the end of each heat preservation stage. When the thickness change rate is less than 0.5% / min, the program automatically enters the next stage.
8. The vacuum hot pressing process for an organosilicon-polyimide composite sealant layer according to claim 1, characterized in that, In step S5, the inert atmosphere is nitrogen or argon, and the gas flow rate is 100-500 sccm; the cooling method is natural cooling with the furnace, and the cooling rate is controlled at 2-5℃ / min.
9. The vacuum hot pressing molding process for an organosilicon-polyimide composite sealant layer according to claim 1, characterized in that, Between steps S3 and S4, there is an additional step of laying a reinforcing layer: a layer of fiber-reinforcing cloth pretreated with a coupling agent is laid on the surface of the pre-cured adhesive layer. The fiber-reinforcing cloth is glass fiber cloth, aramid fiber cloth, or carbon fiber cloth, with a surface density of 20-100 g / m³. 2 Then, vacuum hot pressing is performed.
10. The vacuum hot pressing process for an organosilicon-polyimide composite sealant layer according to claim 1, characterized in that, The substrate is stainless steel, aluminum alloy, ceramic or polyimide composite material; the final composite sealant layer has a thickness of 0.2-3mm, a peel strength of not less than 5N / mm, a thermal decomposition temperature of not less than 450℃, and a compression set of not more than 15% at 200℃.